2022
DOI: 10.1111/jfpp.17211
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and oxidative stability of black cumin oil oleogels prepared with natural waxes

Abstract: In this study, black cumin oil (BCO) oleogel was produced using natural waxes (beeswax: BW, sunflower wax: SFW, and carnauba wax: CW) to offer a healthy alternative to shortening. Oiling-off was observed only in the BW oleogel (3.88 ± 0.02%).The CW oleogel had the lowest E a (354.82 kJ/mol), indicating greater resistance to thermal degradation. The highest G′ and G″ were observed in the CW oleogel, while the lowest was observed in the BW oleogel. All oleogel samples displayed weak gel properties (tan δ > 0.1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Consistent with our own findings, they also observed that the PVs of those oleogel samples increased over time during storage. [22] Gravelle et al [34] reported that oil type and oleogel preparation procedure had a significant effect on the oxidative stability of oleogels. These differences can be explained with the findings of the study conducted by Gravelle et al [34] The delta E value is an important quality criterion and is defined as the change in color during storage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with our own findings, they also observed that the PVs of those oleogel samples increased over time during storage. [22] Gravelle et al [34] reported that oil type and oleogel preparation procedure had a significant effect on the oxidative stability of oleogels. These differences can be explained with the findings of the study conducted by Gravelle et al [34] The delta E value is an important quality criterion and is defined as the change in color during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the SW-and BW-based gels had a higher T m when compared to the control group samples. Orhan and Ero glu [22] reported that oleogels prepared with BCO and 10%-BW and 7%-SW had endothermic peaks at 53 and 64 • C, respectively. Yi et al [20] reported that the crystallization onset (T on ) and peak temperatures (T c ) of GSO oleogels containing 15% BW were 21.73 and 20.45 • C, whereas their melting onset and T m were 24.11 and 40.52 • C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations